Experimental and computational analysis of sound absorption behavior in needled nonwovens. (21st July 2018) - Soltani, Parham; Azimian, Mehdi; Wiegmann, Andreas; Zarrebini, Mohammad
Abstract: In this paper application of X-ray micro-computed tomography ( μ CT) together with fluid simulation techniques to predict sound absorption characteristics of needled nonwovens is discussed. Melt-spun polypropylene fibers of different fineness were made on an industrial scale compact melt spinning line. A conventional batt forming-needling line was used to prepare the needled samples. The normal incidence sound absorption coefficients were measured using impedance tube method. Realistic 3D images of samples at micron-level spatial resolution were obtained using μ CT. Morphology of fabrics was characterized in terms of porosity, fiber diameter distribution, fiber curliness and pore size distribution from high-resolution realistic 3D images using GeoDict software. In order to calculate permeability and flow resistivity of media, fluid flow was simulated by numerically solving incompressible laminar Newtonian flow through the 3D pore space of realistic structures. Based on the flow resistivity, the frequency-dependent acoustic absorption coefficient of the needled nonwovens was predicted using the empirical model of Delany and Bazley (1970) and its associated modified models. The results were compared and validated with the corresponding experimental results. Based on morphological analysis, it was concluded that for a given weight per unit area, finer fibers yield to presence of higher number of fibers in the samples. This results in formation of smaller and more tortuous pores, which in turn leads to increase in flow resistivity of media. It was established that, among the empirical models, Mechel modification to Delany and Bazley model had superior predictive ability when compared to that of the original Delany and Bazley model at frequency range of 100–5000 Hz and is well suited to polypropylene needled nonwovens. Graphical abstract: Image 1 Highlights: Combined application of X-ray μ CT and modern computer simulation was introduced. Fabrics were characterized in terms of porosity, fiber diameter and pore size. Effect of micro-structure on sound absorption behavior of nonwovens was studied. Sound absorption behavior of realistic nonwoven structures was modeled. Good agreement between the results and those of published literature was observed.